Design and performance test of a seed metering device for paddy seeder - Syed Abd. Majid, Syed Abd. Hakim (2008)
A vertical disc type metering device for paddy direct seeder was designed, developed and tested metering to safely place pre-germinated paddy seed at equal distance and relatively similar amount. Seed dimension as well as its natural characteristic has been taken into account in designing process. During these experiments only seeds of MR220 variety were utilized. The experiments were carried out on various occasions. The metering component of the device has undergone multiple testing in the laboratory. Likewise the entire device was experimented manually and mechanically on the real ground. Through the experiment, it has been found that this metering device is so much influenced by the existence of moisture around the seeds. In other words, seed with less moisture content will leave the device at ease in contrast to wet seeds. Nevertheless the introduction of air flowing through the seed container helps the wet seeds to be dispatched. Experiments indicate that the metering device has managed to deliver at the average of five dry paddy seed in a drop. It was also found that with the assistance of air blowing through the seed container, this device is capable of delivering at the average of three wet paddy seed at once. Apart from the number of seeds dropped, it was also established that despite various treatments applied, drop spacing remains at 22cm apart.